STUDY ON THE EFFECTS OF APPLYING THE PRINCIPLE OF EQUAL RIGHTS AND EQUAL OPPORTUNITIES - OANA RĂVAŞ (Annals of the University of Petrosani: Economics)
The concept of "equality" today means something more than the equal rights that the democrats of the last century enthusiastically claimed for all citizens; it means a real equality of individual opportunities for social promotion, and education is the most important tool in development. Equal opportunities are the concept according to which all human beings are free to develop their personal abilities and to choose without limitations imposed by strict roles. the principles of equal opportunities and non-discrimination are often considered fundamental features of a just society. Both involve a comparative reporting to individuals, groups and values and both are defined as tools to ensure fairness in the public sphere. At the same time, the two can be understood both as a set of formal rules and as moral norms, whose relative weight is given by the general conception of justice to which a certain society adheres.